"On water" ultrasound-assisted one pot efficient synthesis of functionalized 2-oxo-benzo[1, 4]oxazines: First application to the synthesis of anticancer indole alkaloid, Cephalandole A. Issue 22 (31st May 2017) - Jaiswal, Pradeep K.; Sharma, Vashundhra; Prikhodko, Jaroslav; Mashevskaya, Irina V.; Chaudhary, Sandeep
Graphical abstract: Highlights: "On water" ultrasound-assisted efficient synthesis of 2-oxo-benzo[1, 4]oxazines is reported. 2-Oxo-quino[1, 4]oxalines were synthesized using this new methodology. Gram scale synthesis of 2-oxo-benzo[1, 4]oxazines. Green practical synthesis of Cephalandole A using our optimized methodology. Abstract: For the first time, an efficient, simple, synthetic green protocol for the one-pot synthesis of functionalized 2-oxo-benzo[1, 4]oxazines24 –29 in water under ultrasound irradiation is presented. As compared to conventional methods, the present protocol avoids traditional chromatography and purification steps and furnished the target molecules in excellent yields (upto 98%) with no side products. The methodology was also demonstrated on gram scale synthesis. Moreover, functionalized 2-oxo-quinoxaline analogues31 –33, another class of bio-active heterocyclic scaffolds, were also prepared using this method. For the first time, this protocol was successfully applied in the synthesis of the anticancer indole alkaloid, Cephalandole A35 .